The Effect of Employee Turnover on Organizations (Case Study of Electricity Company of Ghana, Cape Coast) - Ampomah, Philipina; Cudjor, Samuel K. (Asian Journal of Social Sciences and Management Studies, 2015)
This study focused on the effect of employee turnover on organizations with reference to the Electricity Company of Ghana (ECG). High employee turnover rates may jeopardize efforts to attain organizational objectives. In addition, when an organization loses a critical employee, the effects on innovation, consistency in providing service to customers and timely delivery of services to customers may be negatively affected. The research design used in this study was the quantitative approach, which allowed the researcher to use structured questionnaires in collecting data. The simple random sampling technique was used to select forty respondents from all levels of management in the company. A high response rate of 95% was obtained using the personal method of data collection, based on which the analysis was made using the frequency tables. The study found that lack of promotion was the primary cause of employee turnover in ECG. Turnover, however, had dual effects on the organization; positive and negative effects. Whiles employee turnover introduced new ideas and skill into the company; it’s also led to difficulties in attracting new staff. To reduce the rate of turnover, management should review condition of service for employees; and also ensure that the working environment is conducive.